Method for detecting electrolyte residual quantity on surface of carbon fiber

By using deionized water on the carbon fiber surface to extract electrolyte residues and measuring the conductivity of the solution to be tested, the problem of difficulty in accurately detecting the electrolyte residues on the carbon fiber surface in the prior art is solved, and the performance and life of the composite material are improved.

CN119510509APending Publication Date: 2025-02-25ZHONGFU SHENYING CARBON FIBER LIANYUNGANG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411701490.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to accurately detect the electrolyte residue on the surface of carbon fiber, which affects the bonding interface performance of carbon fiber and resin and reduces the service performance and life of composite materials.

Method used

By placing the carbon fiber in deionized water, the electrolyte residue is extracted, and the conductivity of the solution to be measured after the capacity is fixed, so as to accurately determine the electrolyte residue on the surface of the carbon fiber.

Benefits of technology

Accurate detection of the electrolyte residue on the surface of carbon fiber is achieved, helping to optimize the washing process and improve the mechanical properties and service life of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510509A_ABST
    Figure CN119510509A_ABST
Patent Text Reader

Abstract

The invention provides a carbon fiber surface electrolyte residual quantity detection method, which comprises: placing a first preset mass of carbon fiber in a container, adding a second preset mass of deionized water into the container, and extracting an electrolyte on the surface of the carbon fiber under a preset condition to obtain an electrolyte leachate; transferring the electrolyte leaching solution to a volumetric flask, and fixing the volume of the electrolyte leaching solution to a third preset mass to obtain a solution to be detected; the conductivity of the solution to be detected is obtained, and the electrolyte residual quantity on the surface of the carbon fiber is obtained. According to the method provided by the invention, the electrolyte concentration of the to-be-detected solution in unit volume is accurately represented by measuring the electrolyte of the to-be-detected solution, so that the electrolyte residual quantity on the surface of the carbon fiber can be accurately determined, and process control and quality detection in a carbon fiber production process are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of trace detection technology, and in particular to a method for detecting residual electrolyte on the surface of carbon fiber. Background Art

[0002] Due to its excellent mechanical properties, polyacrylonitrile carbon fiber has been widely used in many fields as a high-performance reinforcement material. It is an important strategic basic material and a typical new military and civilian dual-use material. When carbon fiber is used as a reinforcement base in composite materials, the carbon fiber needs to be tightly combined with the resin. Therefore, the interfacial performance of the carbon fiber needs to be improved. At present, the surface of the carbon fiber is usually modified by electrochemical anodization of the carbon fiber using an electrolyte solution, so that oxygen-containing and nitrogen-containing active groups are generated on the surface of the carbon fiber to improve the wettability and adhesion of the carbon fiber. These active groups can effectively combine with the oxygen-containing groups in the resin to enhance the interfacial adhesion of the composite material, thereby improving the interlaminar shear strength of the composite material.

[0003] After the surface modification of carbon fiber, a certain amount of electrolyte will remain on the surface of the carbon fiber, and a water washing process is usually used to remove the electrolyte on the surface of the carbon fiber as much as possible. After the water washing process, if there is still a large amount of electrolyte residue on the surface of the carbon fiber, the residual electrolyte will easily affect the bonding interface performance between the carbon fiber and the resin, and the carbon fiber will not be able to provide good mechanical properties for the composite material, reducing the performance and life of the carbon fiber composite material. Therefore, by testing the amount of electrolyte residue on the surface of the carbon fiber that has undergone the water washing process, on the one hand, the quality of the carbon fiber can be tested, and on the other hand, the process of the water washing process can be adjusted and optimized based on the test results.

[0004] At present, the electrolyte on the surface of the carbon fiber is usually extracted by placing the washed carbon fiber in a water bath, and then a pH indicator or pH meter is used to measure the solution after the water bath, and the presence of electrolyte residue is determined by observing the color of the pH indicator or the pH value read by the pH meter. This method is heavily dependent on personnel experience, and the pH value cannot accurately represent the amount of electrolyte residue. Summary of the invention

[0005] In order to overcome the problems existing in the related art, the present disclosure provides a method for detecting the residual electrolyte on the surface of carbon fiber.

[0006] A method for detecting residual electrolyte on the surface of carbon fiber, the detection method comprising:

[0007] Placing a first preset mass of carbon fiber in a container, adding a second preset mass of deionized water into the container, and extracting electrolyte on the surface of the carbon fiber under preset conditions to obtain an electrolyte leachate;

[0008] Transferring the electrolyte leaching solution to a volumetric flask, and adjusting the electrolyte leaching solution to a third preset mass to obtain a solution to be tested;

[0009] The conductivity of the solution to be tested is obtained to obtain the residual electrolyte on the surface of the carbon fiber.

[0010] According to some embodiments of the present disclosure, obtaining the conductivity of the solution to be tested and obtaining the residual electrolyte on the surface of the carbon fiber includes:

[0011] Acquiring configuration information, where the configuration information is used to characterize a corresponding relationship between electrolyte concentration and conductivity;

[0012] The conductivity of the solution to be tested is obtained, and based on the conductivity and the configuration information, the residual amount of electrolyte on the surface of the carbon fiber is determined.

[0013] According to some embodiments of the present disclosure, the method for establishing the configuration information includes:

[0014] Preparing a plurality of electrolyte standard solutions, each of the electrolyte standard solutions having a different concentration;

[0015] The test conductivity of each of the electrolyte standard solutions is obtained, and a standard curve is fitted based on the concentrations of the plurality of electrolyte standard solutions and the test conductivity, as the configuration information.

[0016] According to some embodiments of the present disclosure, the first preset quality is less than the second preset quality and less than the third preset quality.

[0017] According to some embodiments of the present disclosure, the ratio of the first preset quality to the third preset quality is 1:25.

[0018] According to some embodiments of the present disclosure, the preset conditions include: extraction temperature 98°C-100°C, extraction time 30min-80min.

[0019] According to some embodiments of the present disclosure, the electrolyte includes at least one of sodium hydroxide, ammonium carbonate, sulfuric acid, and nitric acid.

[0020] According to some embodiments of the present disclosure, obtaining the conductivity of the solution to be tested includes:

[0021] The solution to be tested is tested using a conductivity meter to obtain the conductivity of the solution to be tested.

[0022] According to some embodiments of the present disclosure, before transferring the electrolyte leachate, the detection method further includes:

[0023] The electrolyte leachate is cooled to 20°C-25°C.

[0024] According to some embodiments of the present disclosure, before the electrolyte leaching solution is fixed to a third preset mass, the detection method further includes:

[0025] The container and the transfer device of the electrolyte leaching solution are cleaned with deionized water to obtain a cleaning solution, and the cleaning solution is transferred to the volumetric flask.

[0026] The technical solution provided by the embodiment of the present disclosure may include the following beneficial effects: extracting the electrolyte on the surface of the carbon fiber of the first preset mass by deionized water of the second preset mass, and fixing the electrolyte leaching solution to the third preset mass to obtain a test solution, and then obtaining the conductivity of the test solution, and using the conductivity to characterize the electrolyte residue on the surface of the carbon fiber. The method provided by the present disclosure measures the electrolyte of the test solution to accurately characterize the electrolyte concentration of the test solution per unit volume, thereby accurately determining the electrolyte residue on the surface of the carbon fiber, which is beneficial to process control and quality inspection in the carbon fiber production process.

[0027] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0029] Figure 1 It is a flow chart of a method for detecting residual electrolyte on the surface of carbon fiber, showing an exemplary embodiment. DETAILED DESCRIPTION

[0030] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of devices and methods consistent with some aspects of the present invention as detailed in the appended claims.

[0031] Due to its excellent mechanical properties, polyacrylonitrile carbon fiber has been widely used in many fields as a high-performance reinforcement material. It is an important strategic basic material and a typical new military and civilian dual-use material. When carbon fiber is used as a reinforcement base in composite materials, the carbon fiber needs to be tightly combined with the resin. Therefore, the interfacial performance of the carbon fiber needs to be improved. At present, the surface of the carbon fiber is usually modified by electrochemical anodization of the carbon fiber using an electrolyte solution, so that oxygen-containing and nitrogen-containing active groups are generated on the surface of the carbon fiber to improve the wettability and adhesion of the carbon fiber. These active groups can effectively combine with the oxygen-containing groups in the resin to enhance the interfacial adhesion of the composite material, thereby improving the interlaminar shear strength of the composite material.

[0032] After the surface modification of carbon fiber, a certain amount of electrolyte will remain on the surface of carbon fiber, and a water washing process is usually used to remove the electrolyte on the surface of carbon fiber as much as possible. After the water washing process and the drying process, if there is still a large amount of electrolyte residue on the surface of carbon fiber, the residual electrolyte will easily affect the bonding interface performance between carbon fiber and resin, and the carbon fiber will not be able to provide good mechanical properties for the composite material, reducing the performance and life of the carbon fiber composite material. Therefore, by testing the amount of electrolyte residue on the surface of carbon fiber that has undergone the water washing process and the drying process, on the one hand, the quality of carbon fiber can be tested, and on the other hand, the process of the water washing process can be adjusted and optimized based on the test results.

[0033] At present, the electrolyte on the surface of carbon fiber is usually extracted by placing the carbon fiber in a water bath after washing and drying, and then a pH indicator or pH meter is used to measure the solution after the water bath, and the presence of electrolyte residue is determined by observing the color of the pH indicator or the pH value read by the pH meter. This method is heavily dependent on personnel experience, and the pH value cannot accurately represent the amount of electrolyte residue.

[0034] In view of this, the present disclosure provides a method for detecting the residual amount of electrolyte on the surface of carbon fiber, comprising: placing a first preset mass of carbon fiber in a container, and adding a second preset mass of deionized water to the container, extracting the electrolyte on the surface of the carbon fiber under preset conditions to obtain an electrolyte leaching solution; transferring the electrolyte leaching solution to a volumetric flask, and fixing the electrolyte leaching solution to a third preset mass to obtain a solution to be tested; obtaining the conductivity of the solution to be tested to obtain the residual amount of electrolyte on the surface of the carbon fiber. The method provided by the present disclosure measures the electrolyte of the solution to be tested to accurately characterize the electrolyte concentration of the solution to be tested per unit volume, thereby accurately determining the residual amount of electrolyte on the surface of the carbon fiber, which is beneficial to process control and quality detection in the production process of carbon fiber.

[0035] An exemplary embodiment of the present disclosure provides a method for detecting residual electrolyte on the surface of carbon fiber, referring to Figure 1 As shown, Figure 1 This is a flow chart of a method for detecting residual electrolyte on the surface of carbon fiber provided by an exemplary embodiment, and the detection method includes the following steps:

[0036] Step S100, placing a first preset mass of carbon fiber in a container, adding a second preset mass of deionized water into the container, and extracting electrolyte on the surface of the carbon fiber under preset conditions to obtain an electrolyte leachate;

[0037] Step S200, transferring the electrolyte leaching solution to a volumetric flask, and adjusting the electrolyte leaching solution to a third preset mass to obtain a solution to be tested;

[0038] Step S300, obtaining the conductivity of the solution to be tested, and obtaining the residual electrolyte on the surface of the carbon fiber.

[0039] In step S100, the carbon fiber is a carbon fiber that has undergone an electrochemical anodization process, a water washing process, and a drying process in sequence, but has not been sizing treated, and residual electrolyte may exist on its surface. The composition of the electrolyte remaining on the surface of the carbon fiber is the same as the composition of the electrolyte used by the carbon fiber for the electrochemical anodization process, and the electrolyte may include at least one of sodium hydroxide, ammonium carbonate, ammonium bicarbonate, sulfuric acid, and nitric acid. In some examples, a strong electrolyte may be used for the electrochemical anodization process, and the electrolyte may include at least one of sodium hydroxide, ammonium carbonate, sulfuric acid, and nitric acid.

[0040] In this step, a first preset mass of carbon fiber is placed in a container, which can be a reaction vessel such as a beaker or flask that can withstand a certain temperature. The first preset mass can be determined based on experience and the specifications of the volumetric flask (i.e., the third preset mass) for subsequent constant volume of the electrolyte leachate. If the first preset mass is too small, it is easy to make the electrolyte concentration in the solution to be tested obtained after the electrolyte leachate is constant volume too small, resulting in the inability to measure the conductivity, or the inability to reflect the difference in conductivity; if the second preset mass is too large, the electrolyte concentration in the solution to be tested obtained after the electrolyte leachate is constant volume is too large, and the difference in conductivity cannot be reflected. The first preset mass can be a fixed value, or a 1% deviation can be allowed on the basis of the fixed value.

[0041] After placing the first preset mass of carbon fiber in the container, add the second preset mass of deionized water to the container. The deionized water serves as a solvent for the electrolyte on the surface of the carbon fiber. The electrolyte can be detached from the surface of the carbon fiber and dissolved in the deionized water to obtain an electrolyte leachate. To ensure the extraction effect of the electrolyte, the second preset mass of deionized water needs to completely immerse the first preset mass of carbon fiber. Therefore, the second preset mass>first preset mass can be set. Of course, since the second preset mass of deionized water obtains an electrolyte leachate after extracting the electrolyte, and the electrolyte leachate will be fixed to the third preset mass later, the second preset mass should be less than the third preset mass to avoid the electrolyte leachate exceeding the third preset mass when the volume is fixed. In other words, the first preset mass should be set to <second preset mass<third preset mass.

[0042] After adding a second preset mass of deionized water into the container, the electrolyte on the surface of the carbon fiber is extracted into the deionized water under preset conditions, and the deionized water and the electrolyte dissolved therein form an electrolyte leachate. The preset conditions may be conditions that allow the electrolyte on the surface of the carbon fiber to be fully dissolved in the deionized water. For example, the process of extracting the electrolyte may be heating the container, and the preset conditions may include extraction temperature and extraction time.

[0043] Since the water washing temperature in the water washing process of carbon fiber is usually between 55℃-65℃, if the extraction temperature is equal to or less than the water washing temperature of the water washing process, the electrolyte remaining on the surface of the carbon fiber may not be completely extracted, which is easy to affect the final test results. In some examples, the preset conditions may include: extraction temperature 98℃-100℃, extraction time 30min-80min. That is, the container can be placed at 98℃-100℃, or the deionized water in the container can be heated to 98℃-100℃ for 30min-80min, so that the electrolyte firmly attached to the surface of the carbon fiber is dissolved in the deionized water to obtain an electrolyte leachate. It is understood that during the extraction of the electrolyte, the deionized water and carbon fiber in the container can be stirred regularly to accelerate or fully dissolve the electrolyte. In some examples, the preset conditions may include: extraction temperature 100℃, extraction time 30min-60min. In some examples, the carbon fiber is boiled and extracted for 30min-60min.

[0044] In step S200, the electrolyte leachate in the container is transferred to a volumetric flask, the carbon fiber in the container can be taken out, and the electrolyte leachate in the container can be transferred using a stirring rod or a glass rod. At the same time, the taken out carbon fiber can be squeezed and washed multiple times (at least three times) with a small amount of deionized water, and the washing liquid is transferred to the volumetric flask. In some examples, a small amount of deionized water can also be used to wash the container for extracting the electrolyte leachate multiple times, and the transfer device (such as a stirring rod or a glass rod) of the electrolyte leachate can be washed multiple times with deionized water to obtain a washing liquid, and the washing liquid is transferred to the volumetric flask.

[0045] The apparatus and carbon fiber in contact with the electrolyte leachate are cleaned to obtain a cleaning solution, and the cleaning solution is transferred to a volumetric flask to prevent the electrolyte leachate from remaining on the apparatus and affecting the concentration of the solution to be tested, thereby affecting the subsequent test results. It is understandable that the sum of the mass of the electrolyte leachate and the mass of the cleaning solution generated during subsequent cleaning must be less than the third preset mass to avoid the inability to set the electrolyte leachate to a fixed volume and to avoid inaccurate concentration of the solution to be tested.

[0046] After the electrolyte leachate and the cleaning solution are transferred to the volumetric flask, the electrolyte leachate in the volumetric flask is fixed to the volumetric flask specification with deionized water, that is, deionized water is added to the volumetric flask so that the mass of the solution in the volumetric flask reaches the third preset mass, thereby obtaining the solution to be tested. It should be noted that the specification unit of the volumetric flask is generally volume, such as 5ml, 25ml, 50ml, 100ml, 250ml, 500ml, 1000ml, etc. Since the electrolyte concentration on the surface of the carbon fiber is not high, and in order to facilitate the unit unification, it can be approximately considered that the density of the solution to be tested obtained by the final fixed volume is the same as the density of deionized water, therefore, the third preset mass is the product of the specification of the adopted volumetric flask and the density of the solution to be tested (approximately 1). For example, when the specification of the volumetric flask is 250ml, the electrolyte leachate is fixed to 250ml, and it can be considered that the third preset mass is 250g, and the solution to be tested is obtained.

[0047] Since the electrolyte leachate extracted from the carbon fiber surface will eventually be transferred to a volumetric flask for constant volume to form a certain volume of the solution to be tested, the concentration of the solution to be tested is affected by the specifications of the volumetric flask (the third preset mass, which determines the amount of solvent in the solution to be tested) and the mass of the carbon fiber from which the electrolyte is extracted (the first preset mass, which determines the amount of solute in the solution to be tested). Therefore, by limiting the relationship between the first preset mass and the third preset mass, these two influencing factors can be eliminated, so that the concentration of the solution to be tested is only related to the residual amount of electrolyte on the carbon fiber surface.

[0048] In some examples, the ratio of the first preset mass to the third preset mass is limited to 1:25, so that the concentration of the solution to be tested can well characterize the electrolyte residue on the surface of the carbon fiber. For example, when 10±0.1g of carbon fiber is weighed for electrolyte residue detection, a 250ml volumetric flask can be used for constant volume. When 20±0.2g of carbon fiber is weighed for electrolyte residue detection, a 500ml volumetric flask can be used for constant volume. In this way, the concentration of the solution to be tested is only related to the electrolyte residue on the surface of the sampled carbon fiber.

[0049] In some examples, before transferring the electrolyte leachate to a volumetric flask, since the temperature of the electrolyte leachate after the electrolyte extraction is relatively high and since the temperature affects the volume of the solution, in order to avoid deviations in the subsequent volume determination of the electrolyte leachate, the electrolyte leachate needs to be cooled to 20°C-25°C to eliminate the effect of temperature on the volume of the solution, and then the cooled electrolyte leachate is transferred to a volumetric flask.

[0050] In step S300, the resistance of a certain volume of electrolyte solution follows Ohm's law, that is:

[0051] R = ρ × I / A (Formula 1)

[0052] Where R is the resistance of the electrolyte solution, ρ is the resistivity, I is the length of the conductivity cell, and A is the cross-sectional area of ​​the conductivity cell.

[0053] Let the conductivity cell constant k cell =A / I (Formula 2), conductivity cell constant k cell It is determined by the size of the conductivity cell, that is, by the volume of the solution being tested.

[0054] Taking the inverse of both sides of (Equation 1), we get 1 / R = 1 / ρ × A / I (Equation 3)

[0055] Let: conductivity G = 1 / R (Equation 4), and conductivity k = 1 / ρ (Equation 5)

[0056] Substituting (Formula 2), (Formula 4), and (Formula 5) into (Formula 3) we can obtain:

[0057] Conductivity G = k × k cell (Formula 6)

[0058] It can be seen from (Formula 6) that the greater the conductivity k of the electrolyte solution, the greater the conductivity G, and the stronger the conductivity of the electrolyte solution. As the concentration of the electrolyte solution increases, the number of ions in the solution increases, the conductivity is enhanced, and the conductivity k also increases. Therefore, a certain volume of the solution to be tested can be set in a device for detecting the conductivity of the electrolyte solution, and a conductivity cell can be used to hold the solution to be tested to obtain the conductivity of the solution to be tested. Conductivity can characterize the concentration of the electrolyte in the solution to be tested, and thus can characterize the electrolyte residue on the surface of the carbon fiber.

[0059] It should be noted that, although after the concentration of the electrolyte solution increases to a certain value, the greater the concentration of the electrolyte solution, the greater the interaction force between ions, which in turn leads to a decrease in the conductivity of the solution, however, since the carbon fiber in the present disclosure has undergone a water washing process and a drying process, although there is residual electrolyte on the surface of the carbon fiber, it is only a small amount, and the concentration of the solution to be tested obtained after extraction is not high enough to cause the solution to reach a level of reduced conductivity.

[0060] In some examples, a conductivity meter can be used to test the solution to be tested to obtain the conductivity of the solution to be tested. The conductivity meter can accurately test the conductivity of the solution and can accurately detect the conductivity of the us / cm level. The conductivity meter can be a two-electrode conductivity electrode conductivity meter, a multi-electrode conductivity electrode conductivity meter, a four-electrode conductivity electrode conductivity meter, or an electromagnetic conductivity electrode conductivity meter.

[0061] In some possible implementations, in step S300, obtaining the conductivity of the solution to be tested to obtain the residual electrolyte on the surface of the carbon fiber includes:

[0062] Step S310, obtaining configuration information, where the configuration information is used to characterize the corresponding relationship between electrolyte concentration and conductivity;

[0063] Step S320: Obtain the conductivity of the solution to be tested, and determine the electrolyte residue on the surface of the carbon fiber based on the conductivity and configuration information.

[0064] In step S310, the configuration information may be pre-stored in the electronic device for easy acquisition, and the configuration information is used to characterize the correspondence between the electrolyte concentration and the conductivity in the solution. Exemplarily, the configuration information may be displayed in the form of a curve, with the horizontal axis and the vertical axis being the electrolyte concentration and the conductivity, respectively, so that the electrolyte concentration and the conductivity may correspond well.

[0065] In step S320, the conductivity of the solution to be tested is obtained. For example, a conductivity meter can be used to measure the conductivity of the solution to be tested, and calculations are performed based on the configuration information and the conductivity of the solution to be tested to determine the electrolyte concentration in the solution to be tested, thereby determining the electrolyte residue on the surface of the carbon fiber.

[0066] In some possible implementations, the method for establishing the configuration information in step S310 may include:

[0067] Step S311, preparing a plurality of electrolyte standard solutions, each of which has a different concentration;

[0068] Step S312: acquiring the test conductivity of each electrolyte standard solution, and fitting a standard curve based on the concentrations and test conductivities of the plurality of electrolyte standard solutions as configuration information.

[0069] In step S311, when the concentration of the solution is the same, the conductivity of the solution is different due to the different types of electrolytes. Since the electrolyte for electrochemical anodization of carbon fiber can include at least one of sodium hydroxide, ammonium bicarbonate, ammonium carbonate, sulfuric acid, and nitric acid, and when the electrolyte for electrochemical anodization includes multiple electrolytes, the multiple electrolytes have a certain ratio. Therefore, for each electrolyte solution of each formula used in electrochemical anodization, multiple electrolyte standard solutions are configured, and the concentration of each electrolyte standard solution is different. That is to say, for example, for a formula in which the electrolyte only includes sodium hydroxide, multiple electrolyte standard solutions containing only sodium hydroxide of different concentrations are configured. For another example, for a formula in which the electrolyte includes sulfuric acid and nitric acid, based on the ratio of sulfuric acid and nitric acid in the electrolyte solution used in electrochemical anodization, multiple electrolyte standard solutions containing sulfuric acid and nitric acid of the same ratio are configured. Therefore, for each electrolyte solution formula, multiple electrolyte standard solutions of different concentrations are configured to meet the test requirements.

[0070] In step S312, a conductivity meter is used to test the test conductivity of multiple electrolyte standard solutions of different concentrations corresponding to each electrolyte solution formula, and for each electrolyte solution formula, data fitting is performed based on the concentrations of multiple electrolyte standard solutions and the corresponding test conductivity to obtain a standard curve for each electrolyte solution formula, and the standard curve can characterize the corresponding relationship between the concentration of the electrolyte standard solution and the test conductivity in the electrolyte solution formula. A curve diagram containing standard curves corresponding to multiple electrolyte solution formulas is used as configuration information. In this way, when determining the electrolyte residue on the surface of the carbon fiber, after obtaining the conductivity of the solution to be tested, the corresponding standard curve can be selected in the configuration information based on the formula of the electrolyte solution used in the electrochemical anodization of the carbon fiber, so as to determine the concentration of the solution to be tested, so as to accurately determine the electrolyte residue on the surface of the carbon fiber.

[0071] The present disclosure is described below in conjunction with specific embodiments.

[0072] Example 1

[0073] Weigh 10.021g of carbon fiber sample (model SYT49S-12K) after electrochemical anodization, washing and drying but not sizing and place it in a 250ml beaker, add 100g of deionized water to completely immerse the carbon fiber. Heat the beaker with the sample until boiling (the measured temperature is 99.8℃), continue heating for 30min after boiling, and stir the sample and deionized water in the beaker every 5min. After heating, the electrolyte leaching solution is obtained, the beaker is placed at room temperature to cool down to room temperature (the measured temperature is 24.8℃), take out the carbon fiber sample in the beaker to another small beaker, and use a glass rod to transfer the electrolyte leaching solution to a volumetric flask with a specification of 250ml. Add 20g of deionized water to the small beaker to squeeze and wash the carbon fiber, and transfer the washing solution to the volumetric flask, and repeat this operation three times. Clean the beaker and glass rod for heating carbon fiber, repeat the operation three times and transfer the cleaning solution to a volumetric flask. Finally, use deionized water to dilute the electrolyte leaching solution in the volumetric flask to 250 ml to obtain the test solution. Based on the operating benchmark of the conductivity meter, a certain amount of the test solution is taken and tested with a conductivity meter, and the conductivity is 6.80us / cm. Subsequently, based on the electrolyte solution formula used in the electrochemical anodization process of SYT49S-12K carbon fiber, select the corresponding standard curve in the configuration information, determine the electrolyte concentration based on the conductivity, and the residual electrolyte on the carbon fiber surface can be characterized.

[0074] Example 2

[0075] Weigh 10.034g of carbon fiber sample (model SYT55S-12K) after electrochemical anodization, washing and drying but not sizing and place it in a 250ml beaker, add 120g of deionized water to completely immerse the carbon fiber. Heat the beaker with the sample until boiling (the measured temperature is 99.8℃), continue heating for 60min after boiling, and stir the sample and deionized water in the beaker every 5min. After heating, the electrolyte leaching solution is obtained, the beaker is placed at room temperature to cool down to room temperature (the measured temperature is 23.5℃), take out the carbon fiber sample in the beaker to another small beaker, and use a glass rod to transfer the electrolyte leaching solution to a volumetric flask with a specification of 250ml. Add 20g of deionized water to the small beaker to squeeze and wash the carbon fiber, and transfer the washing solution to the volumetric flask, and repeat the operation three times. Clean the beaker and glass rod for heating carbon fiber, repeat the operation three times and transfer the cleaning solution to a volumetric flask. Finally, use deionized water to dilute the electrolyte leaching solution in the volumetric flask to 250 ml to obtain the test solution. Based on the operating benchmark of the conductivity meter, take a certain amount of the test solution and test it with the conductivity meter, and the conductivity is 6.35us / cm. Subsequently, based on the electrolyte solution formula used in the electrochemical anodization process of SYT55S-12K carbon fiber, select the corresponding standard curve in the configuration information, determine the electrolyte concentration based on the conductivity, and the residual electrolyte on the carbon fiber surface can be characterized.

[0076] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, article or device that includes the elements.

[0077] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present disclosure.

Claims

1. A method for detecting the residual amount of electrolyte on the surface of carbon fiber, characterized in that: The detection method comprises: Placing a first preset mass of carbon fiber in a container, adding a second preset mass of deionized water into the container, and extracting electrolyte on the surface of the carbon fiber under preset conditions to obtain an electrolyte leachate; Transferring the electrolyte leaching solution to a volumetric flask, and adjusting the electrolyte leaching solution to a third preset mass to obtain a solution to be tested; The conductivity of the solution to be tested is obtained to obtain the residual electrolyte on the surface of the carbon fiber.

2. The method for detecting the residual electrolyte on the carbon fiber surface according to claim 1, characterized in that: Obtaining the conductivity of the solution to be tested and obtaining the residual electrolyte on the surface of the carbon fiber includes: Acquiring configuration information, where the configuration information is used to characterize a corresponding relationship between electrolyte concentration and conductivity; The conductivity of the solution to be tested is obtained, and based on the conductivity and the configuration information, the residual amount of electrolyte on the surface of the carbon fiber is determined.

3. The method for detecting the residual electrolyte on the carbon fiber surface according to claim 2, characterized in that: The method for establishing the configuration information comprises: Preparing a plurality of electrolyte standard solutions, each of the electrolyte standard solutions having a different concentration; The test conductivity of each of the electrolyte standard solutions is obtained, and a standard curve is fitted based on the concentrations of the plurality of electrolyte standard solutions and the test conductivity, as the configuration information.

4. The method for detecting the residual amount of electrolyte on the carbon fiber surface according to claim 1, characterized in that: The first preset quality is less than the second preset quality and less than the third preset quality.

5. The method for detecting the residual electrolyte on the carbon fiber surface according to claim 1, characterized in that: The ratio of the first preset quality to the third preset quality is 1:

25.

6. The method for detecting the residual amount of electrolyte on the carbon fiber surface according to claim 1, characterized in that: The preset conditions include: extraction temperature 98°C-100°C, extraction time 30min-80min.

7. The method for detecting the residual electrolyte on the carbon fiber surface according to any one of claims 1 to 6, characterized in that: The electrolyte includes at least one of sodium hydroxide, ammonium carbonate, sulfuric acid and nitric acid.

8. The method for detecting the residual electrolyte on the carbon fiber surface according to any one of claims 1 to 6, characterized in that: The step of obtaining the conductivity of the solution to be tested comprises: The solution to be tested is tested using a conductivity meter to obtain the conductivity of the solution to be tested.

9. The method for detecting the residual electrolyte on the carbon fiber surface according to any one of claims 1 to 6, characterized in that: Before transferring the electrolyte leachate, the detection method further comprises: The electrolyte leachate is cooled to 20°C-25°C.

10. The method for detecting the residual electrolyte on the carbon fiber surface according to any one of claims 1 to 6, characterized in that: Before the electrolyte leaching solution is fixed to a third preset mass, the detection method further includes: The container and the transfer device of the electrolyte leaching solution are cleaned with deionized water to obtain a cleaning solution, and the cleaning solution is transferred to the volumetric flask.